Chloroquine resistant Plasmodium vivax: in vitro characterisation and association with molecular polymorphisms. - Suwanarusk, R; Russell, B; Chavchich, M; Chalfein, F; Kenangalem, E; Kosaisavee, V; Prasetyorini, B; Piera, K; Barends, M; Brockman, A; Lek-Uthai, U; Anstey, N; et al. (Public Library of Science, 2007)
BACKGROUND: Treatment failure of chloroquine for P. vivax infections has reached high levels in the eastern provinces of Indonesia, however, in vitro characterization of chloroquine resistance and its associated molecular profile have yet to be determined. METHODS: Using a modified schizont maturation assay we investigated the in vitro chloroquine susceptibility profile and molecular polymorphisms of P. vivax isolates collected from Papua, Indonesia, where high levels of clinical chloroquine treatment failure have been reported, and from Thailand, where chloroquine treatment is generally effective. RESULTS: The geometric mean chloroquine IC(50) for P. vivax isolates from Papua (n = 145) was 312 nM [95%CI: 237-411 nM] compared to 46.8 nM [95%CI: 34.7-63.1 nM] from Thailand (n = 81); p<0.001. Correlating with the known clinical efficacy of the area, a cut off for chloroquine resistance was defined as 220 nM, a level exceeded in 13.6% (11/81) of Thai isolates and 65% (94/145) of Papuan isolates; p<0.001. Several sequence polymorphisms in pvcrt-o and pvmdr1, and difference in pvmdr1 copy number were identified. A Y976F mutation in pvmdr1 was present in 96% (123/128) of Papuan isolates and 25% (17/69) of Thai isolates; p<0.001. Overall, the geometric mean chloroquine IC(50) in isolates with the Y976F mutation was 283 nM [95%CI: 211-379], compared to 44.5 nM [95%CI: 31.3-63.4] in isolates with the wild type; p< 0.001. Pvmdr1 amplification occurred in 23% (15/66) of Thai isolates compared to none (0/104) of Indonesian isolates (p<0.001), but was not associated with increased chloroquine resistance after controlling for geographical location. CONCLUSIONS: In vitro susceptibility testing of P. vivax discriminates between populations with differing levels of clinical efficacy of chloroquine. The pvmdr1 polymorphism at Y976F may provide a useful tool to highlight areas of emerging chloroquine resistance, although further studies defining its clinical correlates are needed.